Penggunaan Alat Peraga dalam Metode Bercerita untuk Meningkatkan Perbendaharaan Kata Anak 5-6 Tahun - Ade Agusriani; Siti Sumiati; Wahyuni Ismail; Andi Nurhayati; St Rachmatiah (KHIDMAH: Jurnal Pengabdian Masyarakat, 2022)
Improving vocabulary in children is very important to be stimulated, , the more vocabulary mastered by children it can facilitate children in interacting and communicating with others. This study aims to determine whether the vocabulary mastered by children is able to re-discuss the story that has been heard through the method of storytelling using props in children aged 5-6 years. Community service research in the form of service learning was conducted in kindergarten Aisyiyah Branch 1 Sungguminasa with a number of participants as many as 3 children. The instruments used in the form of props are images of animals that are cut out according to their shape and pasted on cardboard paper, besides the instruments used are also sheets of evaluation of implementation and intervention. Data were analyzed using descriptive statistics. The results of this study showed that the 3 participants ' language development was different, there were children who had dared to propose to retell stories that had been heard but still could not tell them in order, there were also children who could tell it well but needed more time because they were still hesitant and shy and among them there were children who only heard and listened to their friends tell stories. The findings in this study imply that storytelling methods can improve children's vocabulary, if they focus on listening and listening to the content of the story.